2019
DOI: 10.1016/j.worlddev.2019.05.027
|View full text |Cite
|
Sign up to set email alerts
|

The poverty impacts of improved cowpea varieties in Nigeria: A counterfactual analysis

Abstract: Highlights We examine the impact of improved cowpea adoption on poverty in Nigeria. We use a unique and recent nationally representative survey data. Adoption leads to an increase in household income and asset ownership. Poverty reduces with the adoption of improved cowpea varieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 50 publications
13
55
0
2
Order By: Relevance
“…Even when old models like multinomial logit are used, studies attempt to control for endogeneity (Nguyen-Van, Poiraud, To-The 2017; Larsen 2019). Recent studies incorporate technology adoption in single-step impact evaluation models using Heckman models (Ouma and De Groote 2011; Awotide, Karimov, Diagne 2016) and switching regressions (Khonje et al 2015;Shiferaw et al 2014;Manda et al 2019).…”
Section: Move Towards Dynamics Of Adoptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even when old models like multinomial logit are used, studies attempt to control for endogeneity (Nguyen-Van, Poiraud, To-The 2017; Larsen 2019). Recent studies incorporate technology adoption in single-step impact evaluation models using Heckman models (Ouma and De Groote 2011; Awotide, Karimov, Diagne 2016) and switching regressions (Khonje et al 2015;Shiferaw et al 2014;Manda et al 2019).…”
Section: Move Towards Dynamics Of Adoptionmentioning
confidence: 99%
“…The education level of farmers in MP is lower, with 34 percent of households having no formal schooling. Education can enhance the ability to decipher information for the adoption of modern and improved technology (Besley and Case 1993;Katare et al 2013); studies showed that, in Nigeria, those with at least six years of education were more likely to switch over to new improved varieties of cowpea (Manda et al 2019). The average soybean farmer is a smallholder owning only 4.28 acres of land, but the size of the average landholding differs significantly in these two states.…”
Section: Soybean Farm Households and Varietal Adoptionmentioning
confidence: 99%
See 2 more Smart Citations
“…is a crop that plays an important role in human and animal nutrition in several countries (CHEN et al, 2017a), constituting an important food source for populations in Latin America, Asia and Africa (CHEN et al, 2017b;TAN et al, 2012). The species Fabaceae, with protein content in grains ranging from 22 to 30% (MANDA et al, 2019;WENG et al, 2019), is traditionally cultivated in semi-arid regions, such as the Brazilian northeast (ANATALA et al, 2014) due to its high plasticity, especially to conditions with low water availability (RUSINAMHODZI et al, 2012).…”
Section: Introductionmentioning
confidence: 99%